FACTORS INFLUENCING SELECTION OF LEAN TOOLS AND TECHNIQUES IN MALAYSIAN ORGANISATIONS - Yahya, M. S.; Mohammad, M.; Omar, B.; Sulistyo, B. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
This paper attempts to evaluate 16 factors that should be considered when selecting lean tools and techniques. Lean tools and techniques are typically used to eliminate waste that are produced by defects, waiting time, overproduction, extra motion, extra processing, excess inventory, and unnecessary transportation. The study was conducted in the form of a survey, with data being gathered via purposive sampling. The respondents were chosen based on their involvement in the selection and/or implementation of lean tools and techniques in Malaysia organisations. The respondents were made of practitioners, managers, engineers, executives, consultants, and academics. The surveys indicated that there are ten factors with high agreement levels (>=4.00). These include: (1) Top management’s approval and support, (2) Possible benefits gained after implementation, (3) Aligned with the organisation’s vision, mission and purpose, (4) Aligned with the organisation’s strategic plan and goals, (5) Prove of benefits from other similar organisations, (6) Allocation of resources, (7) Workforce capability, (8) Suitable with the organisation’s culture, (9) Suitable with the organisation’s maturity level, and (10) Suitable with the customers’ and stakeholders’ expectations or requirements. It is hoped that this research will assist organisations in selecting the most appropriate lean tools and techniques to be used in waste reduction.